2022
DOI: 10.3390/cimb44100313
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Bilberry (Vaccinium myrtillus L.)

Abstract: Inflammation is important in the pathogenesis of several chronic diseases. The anti-inflammatory properties of berries have been investigated but the anti-inflammatory activity of bilberry has received little attention and a detailed review is yet to be published. Therefore, we compiled information on the phytochemicals of bilberry and preclinical and clinical studies of its anti-inflammatory properties. The review was based on studies from 2007 to date. Phytoconstituents of bilberries were phenolic acids, org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 82 publications
(109 reference statements)
1
16
0
1
Order By: Relevance
“…Through cell, animal, and human clinical trials, green tea and its main component, EGCG, have been shown to have anti-inflammatory effects ( Ohishi, Goto, Monira, Isemura, & Nakamura, 2016 ). Moreover, bilberry and pomegranate extracts have been reported to have anti-inflammatory activity ( Sharma and Lee, 2022 , Ismail et al, 2012 ). Previous in vitro and in vivo studies have been conducted on the effects of propolis on inflammation ( Pahlavani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through cell, animal, and human clinical trials, green tea and its main component, EGCG, have been shown to have anti-inflammatory effects ( Ohishi, Goto, Monira, Isemura, & Nakamura, 2016 ). Moreover, bilberry and pomegranate extracts have been reported to have anti-inflammatory activity ( Sharma and Lee, 2022 , Ismail et al, 2012 ). Previous in vitro and in vivo studies have been conducted on the effects of propolis on inflammation ( Pahlavani et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The health benefits associated with the consumption of hydrolyzed collagen [22][23][24][25][26][27] as well as other animal-origin active substances such as whey [28][29][30][31] and royal jelly [32][33][34][35] promote them as ideal ingredients for immunomodulation purposes. Moreover, the antioxidant properties of Vaccinium myrtillus [36][37][38][39] and Echinacea purpurea [40][41][42][43], coupled with their anti-inflammatory and antimicrobial effects, sustain their use for promoting immunomodulation and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinium berries, such as blueberries, have been shown to possess comparable antioxidant and anti-inflammatory properties. 22–24 They are easily available to the public and have affordable pricing in comparison to other berries, which makes them attractive to consumers. There are other (poly)phenol-rich berries such as chokeberries ( Aronia melanocarpa ) that have been previously studied as sports supplements, 25 yet they might not be accessible and affordable to most consumers.…”
Section: Introductionmentioning
confidence: 99%